COILing diverse islands: a virtual exchange between the University of the Bahamas and the Borough of Manhattan Community College - Raymond Oenbring; Deniz Gokcora (University of Groningen Press, 2022)
This practice report describes a Collaborative Online International Learning (COIL) exchange between academic writing students at the University of the Bahamas (UB) and English Language Learners (ELLs) at the Borough of Manhattan Community College (BMCC) of the City University of New York (CUNY). While COIL projects and other classroom virtual exchanges between Western and non-Western institutions have often been construed as tools to introduce cultural and linguistic diversity into Western classrooms, this study shows that the opposite is also possible. In our project, a diverse, largely immigrant group of postsecondary students in New York City participated in an intercultural exchange with a more culturally and linguistically homogeneous student group in The Bahamas. The study details the digital media used to initiate the virtual exchange and the specifics of the assignment sequences, including how the authors worked with the springboard text read by both classes (that is, Richard Rodriguez's (1978) noted literacy autobiography 'The Achievement of Desire', where he describes his academic ambitions as the child of Mexican immigrants to the United States).